(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the era of globalization, English has emerged as a dominant medium of communication in international education and the global labor market. This article examines the multifaceted role of English as a bridge language that facilitates access to prestigious academic institutions, enhances cross-cultural communication, and opens doors to career advancement across borders. It highlights how proficiency in English is often a prerequisite for enrollment in international programs, participation in research collaboration, and employment in multinational corporations. Moreover, the paper explores the challenges faced by non-native speakers in acquiring academic and professional fluency, and suggests strategies to overcome linguistic barriers. The study underscores the necessity of integrating English language education into national success in a competitive global environment.